Prescription in International Law - Alexander N. Vylegzhanin; Ekaterina L. Sokolova (Московский журнал международного права)
The article shows that prescription is recognized as a mode of acquisition of territory within International Law. Though there is no term “prescription” in universal international conventions such international treaties do operate with the term “historic title” as an accepted notion. The purpose of prescription is to be a legitimization of continued, factual and uncontested authority of a state over a territory. Different theoretical constructions of prescription in the teachings of specialists in International Law are not supported by International courts and arbitrations. For them what matters is which of the parties in a dispute has a sovereignty over the disputed territory. Nevertheless such courts and arbitrations usually do not consider the status of prescription in the modern International Law.